A review of the state-of-the-art research on carbon structure evolution during the coking process: From plastic layer chemistry to 3D carbon structure establishment. (1st July 2020) - Chen, Yixin; Lee, Soonho; Tahmasebi, Arash; Bai, Jin; Mahoney, Merrick; Yu, Jianglong
Abstract: This paper provides a review of the state-of-the-art research in the open literature on the carbon structure evolution in the semi-coke region following the last stage of the plastic layer transformation. Coking coals exhibit thermoplastic fluid-like behavior due to the change of chemical structures in plastic layers when heated in the coke ovens. Once the temperature of the coal charge exceeds the thermoplastic range, condensation, cross-linking, and repolymerization reactions take place. This results in the formation of a more ordered structure, referred to as semi-coke, with the final release of light gases. A further temperature increase leads to the release of hydrogen from the aromatic hydrocarbon structures with the formation of C–C bonds and, consequently, the carbon structure, which corresponds to the gradual transformation from the semi-coke to high-temperature coke. A variety of advanced analytical techniques have been employed, including infrared spectroscopy (IR), solid-state carbon-13 nuclear magnetic resonance ( 13 C NMR) and X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), and Raman spectroscopy. The carbon structure in coke generally is generally in the form of non-graphitic turbostratic structure, which exhibits isotropic property. There is a lack of information in terms of the 3D carbon structure model of coke/semi-coke and how these structures evolve from hydrocarbon sheets to more stable structures above 500 °C in the coke oven. This review also concludes future research scopes and the limitations of current knowledge.